Influence of EEG-based functional connectivity and inhibitory control on educational web search performance among adolescents - Надежда Владимировна Сутормина (Психология человека в образовании)
Introduction. Digital technologies have become an essential aspect of modern life, necessitating research into their effects on children’s learning processes. Additionally, it is crucial to investigate other factors that impact the successful completion of educational tasks. Brain functional connectivity has been shown to correlate with intellectual abilities and the quality of cognitive task performance. Furthermore, changes in connectivity patterns are associated with learning processes within the brain. Despite this, there is a paucity of research examining functional connectivity metrics in the context of children’s learning. Inhibitory control is another critical parameter that significantly influences learning outcomes. Therefore, this study investigates whether the performance of an educational task utilizing web search is associated with various functional connectivity metrics and inhibitory control.